Old World Mucosal Leishmaniasis Treated with a Single Dose of Amphotericin: A Case Report - Thapaliya, Sabin; Poudyal, Prasanta; Tripathi, Prashant; Thapa, Milan; Shrestha, Anjan (Journal of Institute of Medicine Nepal, 2024)
Mucosal leishmaniasis, an uncommon disease in the old world, is recognized as an occasional complication of donovani related visceral leishmaniasis. It usually affects the spleen, liver, skin, mucosa of the respiratory tract and, less commonly, the oral cavity. Our case was a young adult with non-healing lesions in the oropharyngeal region who was diagnosed as mucosal leishmaniasis during evaluation for suspected mucosal carcinoma. The diagnosis was made with the rK39 strip-test after multiple futile test results. A single dose of liposomal amphotericin B cured the disease.